CLINICAL EFFICACY OF A GEL BASED ON BIO SUBSTANTIATION FROM THE PRODUCTS OF ANTLER MARAL BREEDING IN THE TREATMENT OF GINGIVITIS - Токмакова, Светлана Ивановна; Луницына, Юлия Васильевна; Бондаренко, Ольга Владимировна; Турецкова, Вера Феопеновна; Дворникова, Любовь Габдулбариевна; Кузикова, Виктория Анатольевна; Шевякина, Алёна Олеговна (Medicine in Kuzbass, 2024)
In the Altai Territory, the prevalence of inflammatory periodontal diseases reaches 100%. The chronic progressive recurrent nature of the course determines a comprehensive approach to the treatment of this pathology and the need to find new effective remedies. The aim of the research – to evaluate the clinical effectiveness of a dental gel based on dry maral blood in the complex treatment of gingivitis. Materials and methods. A prospective controlled clinical study was conducted with the participation of 42 volunteers with generalized chronic catarrhal gingivitis. Two numerically equal groups have been formed. In the main one, complex treatment was carried out with the use of a developed gel containing dry maral blood. In the comparison group – traditional treatment. Hygiene index, papillary-marginal-alveolar (PMA) index, bleeding index (SBI) and periodontal index were determined on the day of treatment, 7 and 14 days after the start of the course of therapy. The effectiveness of the treatment was evaluated on the basis of statistical analysis. Results. Before the start of treatment, patients of both groups had high indicators of hygiene index, papillary-marginal-alveolar index, bleeding index and periodontal index, which indicated the presence of generalized inflammation in periodontal tissues. Two weeks later, at the control examination, there was a significant improvement in the condition of periodontal tissues in both groups, characterized by clinical improvement and a significant decrease in the index score relative to the initial values. However, the SBI and PI indices in the main group decreased significantly faster (p < 0.05). The effectiveness of the course of treatment in the group where the developed gel was used was 65-75 %, which was on average 10-30 % higher than the parameters after the traditional treatment regimen. Conclusion. The developed gel based on dry maral blood is effective in the complex treatment of gingivitis in the form of an application. When used for two weeks, the product has a hemostatic, anti-inflammatory effect, improving the functional state of periodontal tissues.